A Review on purple sulphur bacteria for waste Water treatment - Pichandy Muthu prasanna; M.Komala; J.Padmavathy; Dr. P. Bharghava Bhushan Rao; Yuvabharathikannan D; Kannaiyan Suria Prabha (International Journal of Pharma and Bio Sciences, 2020)
Usage of microbes not only limited to antibiotics production but now have extended to waste water treatment. Microbes have made an immense contribution to the cost reduction process. Many chemical processes have been replaced by many biological process due to their cost effectiveness. . Many countries are shifting their strategies for waste and sewage water treatment from chemical techniques to these advantageous microbial techniques. These microbes particularly purple sulfur bacteria decomposes a great range of biological and other organic waste to a less-toxic or non toxic end products. The cost involved in getting these waste water converted to non toxic by-product by these bacteria found to be far more lesser than any other conventional techniques. Thus by providing waste water as a nutrient to this purple bacteria makes a good and great impact on the environment. This review discusses the habitat, mechanism of biodegradation, factors influencing these biodegradation and other related researches concerned with the biodegrading efficiency of Purple sulfur bacteria.